Chronic Fluoxetine Impairs the Effects of 5-HT1A and 5-HT2C Receptors Activation in the PAG and Amygdala on Antinociception Induced by Aversive Situation in Mice - Baptista-de-Souza, Daniela; Tavares, Lígia Renata Rodrigues; Furuya-da-Cunha, Elke Mayumi; Carneiro de Oliveira, Paulo Eduardo; Canto-de-Souza, Lucas; Nunes-de-Souza, Ricardo Luiz; Canto-de-Souza, Azair (Frontiers in Pharmacology, 2020)
Growing evidence suggests an important role of fluoxetine with serotonin 5-HT1A and 5-HT2C receptors in the modulation of emotion and nociception in brain areas such as the amygdala and periaqueductal gray (PAG). Acute fluoxetine impairs 5-HT2C (but not 5-HT1A) receptor activation in the amygdaloid complex. Given that fluoxetine produces its clinical therapeutic effects only when given chronically, this study investigated the effects of chronic treatment with fluoxetine on the effects produced by 5-HT1A or 5-HT2C receptors activation in the amygdala or PAG on fear-induced antinociception. We recorded the effects of chronic fluoxetine on serotonin and 5-HIAA levels as well as serotonin turnover; 5-HT1A and 5-HT2C receptor protein levels in the amygdala and PAG. Also, we evaluated the effects of chronic fluoxetine combined with intra-amygdala or intra-PAG injection of MK-212 (a 5-HT2C agonist; 0.63 nmol) or 8-OH-DPAT (a 5-HT1A agonist; 10 nmol) on the antinociceptive response in mice confined in the open arm of the elevated plus-maze (EPM). Nociception was assessed with the writhing test induced by intraperitoneal injection of 0.6% acetic acid. Results showed that fluoxetine (20 mg/kg, s.c.) enhanced the open-arm induced antinociception (OAA) and reduced the number of writhes in mice confined in the enclosed arm, featuring an analgesic effect. In addition, fluoxetine increased the expression of 5-HT2C receptors and 5-HT levels whereas reduced its turnover in the amygdala. While fluoxetine did not change 5-HT and 5-HIAA levels, and its turnover in the PAG, it up-regulated 5HT1A and 5-HT2C receptors in this midbrain area. Chronic fluoxetine (5.0 mg/Kg, an intrinsically inactive dose on nociception) antagonized the enhancement of OAA produced by intra-amygdala or intra-PAG injection of MK-212. Fluoxetine also impaired the attenuation of OAA induced by intra-amygdala injection of 8-OH-DPAT and totally prevented OAA in mice that received intra-PAG 8-OH-DPAT. These results suggest that (i) 5-HT may facilitate nociception and intensify OAA, acting at amygdala 5-HT1A and 5-HT2C, respectively, and (ii) fluoxetine modulates the OAA through activation of 5-HT2C within the PAG. These findings indicate that chronic fluoxetine impairs the effects of 5-HT1A and 5-HT2C receptors activation in the amygdala and PAG on fear-induced antinociception in mice.